Comparative Study of Biochemical Composition and Nutrient Profile of Four Species of Penaeid Shrimps - Jawahar, Laly Sundarambal; Sankar T. V. (Fishery Technology, 2023)
The biochemical composition and nutrient profile of flower tail shrimp (Metapenaeus dobsoni), brown shrimp (Metapenaeus monoceros), jinga shrimp (Metapenaeus affinis) and kiddi shrimp (Parapenaeopsis stylifera) were evaluated. Significantly higher (p<0.05) content of crude protein in M. affinis (17.84 %) and crude fat in M. monoceros (1.78 %) and ash in P. stylifera (1.84 %) were observed. Glutamic acid (19.45 to 20.45 %) was the predominant amino acid. Ratio of essential to non-essential amino acids (EAA/ NEAA) was 0.74 to 0.89 with highest in case of M. dobsoni. Palmitic acid was the abundant fatty acid in all the four species (15.04 to 21.99 %). The content of eicosapentaenoic acid (13.37 to 14.85 %) and docosahexaenoic acid (8.65 to 16.99 %) were significantly higher. The ratio of n-3 and n-6 fatty acids ranged from 0.52 to 1.05. The ratio of polyunsaturated to saturated fatty acids (PUFA/ SFA) was highest in P. stylifera (1.14), while in the Metapenaeus spp. it ranged from 0.54 to 0.82. Atherogenicity index (AI) and thrombogenicity index (TI) were lower, AI values ranged from 0.53 to 0.68 in Metapenaeus spp. and 0.39 in case of P. stylifera. TI values of Metapenaeus spp. range from 0.46 to 0.53 and in case of P. stylifera TI value was 0.25. The mineral profile showed rich content of potassium, sodium, calcium and magnesium.